Humanitarian health education and training state-of-the-art: a scoping review - Bahattab, Awsan; Trentin, Monica; Hubloue, Ives; Della Corte, Francesco; Ragazzoni, Luca (Frontiers in Public Health, 2024)
Introduction In the past decade, humanitarian emergencies have been increasing, leading to an higher demand for humanitarian health professionalization. Education and training are critical for preparing these workers to provide effective care during crises. Understanding the current state-of-the-art in humanitarian health education is essential to inform research and development of future educational programs. This review surveys the peer-reviewed literature to provide insights into the current thinking in the field. Methods A review was conducted in March 2023 and updated in May 2024 using PubMed, Web of Science, Scopus, and Education Resources Information Center databases for English-language peer-reviewed articles published since January 2013. The review followed the Joanna Briggs Institute methodology for scoping reviews and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). Data were analyzed using qualitative content analysis and presented as a narrative descriptive summary. Results After screening, 32 articles met the inclusion criteria. The themes of the selected articles focus on education and training frameworks, mapping, and programs. Despite the growing opportunities, most education and training programs are based in the Global North. The gaps identified include a lack of standardized curriculum or competency frameworks and evaluation frameworks to guide the development and evaluation of further standardized training programs. Interdisciplinary and collaborative partnerships, iterative design, and mixed teaching methods and modalities, including e-learning, facilitated successful training. However, logistical and technical constraints and the lack of standardized training frameworks were barriers to developing, implementing, and evaluating such training programs. Conclusion This review provides an overview of the humanitarian health education trends over the last decade and identifies key areas for future educational development and research. The findings emphasize the importance of adapting interdisciplinary and collaborative partnerships and prioritizing the training of local staff through regional centers, local leadership, and accessible e-learning, including e-simulation. The review also highlights the need for continued research and evaluation of humanitarian health education and training programs with standardized metrics to evaluate training programs and identify areas for improvement. These steps will help ensure that humanitarian health professionals receive adequate training to provide effective healthcare in crisis situations.